Exploring the impact of family health care implementation on family resilience: Insights from friedman’s structural-functional theory - Utami, Ressa Andriyani; Ramba, Hardin La; Nuraeni, Asti; Baua, Ma Elizabeth C; Locsin, Rozzano; Polnok, Sanglar (Science Midwifery, 2025)
Background The family plays a crucial role in maintaining the health and well-being of its members. One of its essential functions is health care, including disease prevention, caregiving, and health-related decision-making. This function becomes particularly important during times of crisis or illness. Family resilience refers to the ability of a family to adapt, recover, and grow stronger in the face of adversity. A strong health care function within the family may contribute positively to building this resilience. However, the direct relationship between family health care function and family resilience remains underexplored, especially in the Indonesian context. Understanding this relationship is important for developing family-based interventions to promote health and resilience. Therefore, this study aims to examine the correlation between family health care function and family resilience. Objectives This study aims to determine the relationship between the implementation of family health care functions and family reliability. Methods The design of this study is a correlation study with the type of analytical correlation research through a cross sectional study approach Results The results of the bivariate analysis can be concluded that there is a significant relationship between health care function and family resilience in respondents (p = 0.001). The results of the multivariate analysis can be concluded that respondents who have a high income have a 15,897 times chance of having good family reliability compared to those who have a low income. Conclusion The family needs to improve the function of family health care where the family must recognize health problems experienced by family members.